Greening the Workforce: The Role of HRM in Fostering Environmental Citizenship in Nepali Commercial Banks - Chaudhary, Manoj Kumar; Neupane, Krishna; G.C., Suraj; Khadka, Sushma (Journal of Emerging Management Studies, 2025)
Purpose – This study examines the impact of Green Human Resource Management (GHRM) practices on Organizational Citizenship Behavior for the Environment (OCBE) in Nepali commercial banks. Design/methodology/approach - A quantitative research approach was employed using structured questionnaires to collect data from employees of Nepali commercial banks. Correlation and regression analyses were conducted to assess the relationships between GHRM components and OCBE. Findings - The results reveal significant positive correlations (ranging from 0.567 to 0.598) between GHRM practices (Green Recruitment & Selection, Green Training & Development, and Green Performance Appraisal) and OCBE. Regression analysis confirms the significant influence of these practices, except for Green Compensation & Reward, which did not show a statistically significant impact. Conclusion – The study concludes that GHRM practices, particularly recruitment, training, and performance appraisal, play a crucial role in fostering employees’ voluntary environmental behaviors in Nepali banks. However, compensation and rewards do not significantly influence OCBE, suggesting a need for revised incentive structures. Implications – The findings highlight the importance of integrating GHRM into HR policies to promote sustainability. Banks should focus on eco-friendly hiring, training, and appraisal systems while reassessing compensation strategies to better align with environmental goals. Originality/value – This study contributes to the limited literature on GHRM and OCBE in Nepal’s banking sector, offering empirical insights into which HR practices effectively drive environmental citizenship. It provides practical recommendations for policymakers and HR managers aiming to enhance corporate sustainability.